E-commerce industries in Bangladesh and their services: a study on Kinbo Bangladesh Limited - Nazneen, Sabia (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.